A Dynamic Programming Approach To The Maximization Of Output From Production Processes Of Varying Efficiencies - Simone, Albert (Academy of Management Journal, 1967)
Consider a firm which seeks to maximize the output of a given product over a specified planning period. The firm must decide which of the alternative means of production to employ, how intensively to utilize each means selected for employment, and how to allocate its fixed supply of direct labor to these various means. Dynamic programming can be used to make these decisions.